The influence of brand identity, brand image and product quality on repurchasing bodrex flu and batu`k through brand preference (case study at 5 pharmacies in kendari city) - A.wahdania; Sampurno, Sampurno; Sri Widyastuti (SEAN Institute, 2024)
Kombi. This research aims to analyze the influence of brand identity, brand image and product quality on brand preferences which have an impact on repeat purchases of Bodrex flu and cough products in Kendari City. A questionnaire with a closed question design was used as a research instrument, and 100 respondents were sampled in the research. The multiple linear regression method is used as a data analysis technique. In this research, it is known that: Brand identity, brand image, and product quality together have a significant effect on repeat purchases through brand preference.The common cold, common cold or cough and cold are acute respiratory infections (ARI) which are very common among Indonesian people. Generally, sufferers treat colds by taking over-the-counter flu medicines on the market such as Bodrex flu and cough, Komix and OBH